PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA KANTOR JASA PENILAI PUBLIK (KJPP) FIRMANSYAH DAN REKAN CABANG DENPASAR - Ida Ayu Trisna Wijayanthi; Putu Mela Ratini; Argo Dwi Prakoso (Forum Manajemen STIMI Handayani Denpasar, 2020)
Improving the quality of service in a company is a very important and inseparable part of a company. Consumers are satisfied if their expectations are met, and feel very happy if their expectations are exceeded. Likewise with the Public Appraisal Service Firmansyah and Partners in Denpasar engaged in services by providing property valuation services. Seeing the increasing number of competitors, where these competitors have a competitive advantage, especially in terms of the quality of their services, the company is experiencing problems in decreasing the number of users of property valuation services. Based on the description, a study was conducted to find out how the influence of service quality on customer satisfaction at the Public Appraisal Service Office (KJPP) Firmansyah And Denpasar Branch Partners. Based on the results of multiple regression tests using SPSS version 20.0, the results of the study show that partially Physical Evidence, Reliability, Assurance and Empathy variables have no significant positive effect on customer satisfaction of KJPP Firmansyah and Denpasar Partners, and the Responsibility variable has a significant positive effect on KJPP customer satisfaction Firmansyah and Denpasar Partners. While simultaneously Variable Physical Evidence, Reliability, Responsiveness, Assurance and Empathy together have a significant positive effect on customer satisfaction KJPP Firmansyah and Denpasar Partners.